Mechanistic and methodological perspectives on the impact of intense interval training on post-exercise metabolism - Moniz, S. C.; Islam, H.; Hazell, T. J. (Scandinavian Journal of Medicine & Science in Sports, 2020)
The post-exercise recovery period is associated with an elevated metabolism known as excess post-exercise oxygen consumption (EPOC). The relationship between exercise duration and EPOC magnitude is thought to be linear whereas the relationship between EPOC magnitude and exercise intensity is thought to be exponential. Accordingly, near-maximal and supramaximal protocols such as high-intensity interval training (HIIT) and sprint interval training (SIT) protocols have been hypothesized to produce greater EPOC magnitudes than submaximal moderate-intensity continuous training (MICT). This review updates previous reviews by focusing on the impact of HIIT and SIT on EPOC. Research to date suggests small differences in EPOC post-HIIT compared to MICT in the immediate (<1 hour) recovery period, but greater EPOC values post-HIIT when examined over 24 hours. Conversely, differences in EPOC post-SIT are more pronounced, as SIT tends to produce a larger EPOC vs MICT at all time points. We discuss potential mechanisms that may drive the EPOC response to interval training (eg, glycogen resynthesis, mitochondrial uncoupling, and protein turnover among others) and also consider the role of EPOC as one of the potential contributors to fat loss following HIIT/SIT interventions. Lastly, we highlight a number of methodological shortcomings related to the measurement of EPOC following HIIT and SIT.